Undergraduate Students’ Library Interactions: Does Race Shape How Students Experience Library Help? - Connie Strittmatter; Danette V. Day (Evidence Based Library and Information Practice)
Objective – The goal of this study was to examine whether an undergraduate student's race influences their interactions and perceived quality of experiences with librarians/library staff and student employees.